A cloud solution for visualizing and navigating mobile IOT sensor nodes - See, Tian Xin (2019)
This project is to develop a cloud solution for visualizing and navigating mobile IoT sensor nodes. The field of study of this project is related to IoT and distributed system. The problem that this project will solve is to give indoor map support for mobile sensors. So, this project focuses on building a solution to solve the lack of support for mobile IoT sensor nodes and insufficient indoor map support for the existing visualization platforms. As mobile IoT devices are more widely used nowadays, it is a need to have a visualization platform that can fully support mobile IoT devices. The methodology adopted to develop the visualization platform is by using prototyping model. There are two prototypes being produced before developing the final product. The scope of this project is to build an extension from the existing data visualization tools instead of building the whole visualization tool from scratch. It is because there are many existing tools available and it is redundant to build all the existing functions that are available in the market. Some important functions that are included in the visualization platform are able to track the real-time location of the mobile sensors, visualize its current location on an indoor map, and to display different types of data collected from the sensors in a 2D graph. Hence, instead of developing everything from scratch, this project will focus on developing an extension that is able to solve the problem statements as mentioned.